Feel-good or feel-right: The role of moral emotions and other orientation in prosocial behavior in the workplace - Jeong, Sophia Soyoung (ProQuest Dissertations & Theses, 2011)
Recent research surrounding the social intuitionist approach suggests that moral emotions may be a strong motivator for employee prosocial behavior. However, existing literature on prosocial behavior in the workplace has been dominated by cognition-based perspectives, wherein cognitive modes of processing have been the prevalent explanatory mechanisms underlying prosocial behavior. While there have been affect-based explanations for prosocial behavior, they tend to downplay the role of cognitive processing, and adopt a broad perspective of affect that does not distinguish between types of emotions. This dissertation addresses these gaps in the literature by proposing a theoretical model that integrates the two perspectives, and focuses on the mechanisms leading to prosocial behavior, involving motivational orientation, emotions, and cognitive processing. Specifically, I argue that other-orientation influences the extent to which individuals experience moral emotions in conflicts of interest situations, and that moral emotions, in turn, elicit intuitive processing that leads to prosocial behavior. The propositions are tested in two laboratory experiments and one field study.